CASCADED SINGLE-PHASE, PWM MULTILEVEL INVERTER WITH BOOSTED OUTPUT VOLTAGE (Nigerian Journal of Technology, 2020)
Splitting of a dc voltage source with two capacitors has been the approach in generating 5-level output voltage with single- and three-phase full-bridge circuits and added bidirectional switch. Associated with this configuration is the problem of voltage imbalance between the splitting capacitors. In addition, the inverter output voltage magnitude is obviously limited to the value of the split input voltage source. Presented in this paper is a unit topology for single-phase 5-level multilevel inverter, MLI. It simply consists of a full-bridge circuit, a capacitor, charge-discharge unit and a dc source. The charge-discharge unit with the capacitor is the interface between the full-bridge and the dc source. The proposed unit cell can generate a 5-level output voltage waveform whose peak value is twice the input voltage value. For higher output voltage level, a cascaded structure of the developed unit cell is presented. Comparing the proposed inverter with CHB inverter and some recent developed MLI topologies, it is found that the proposed inverter configuration generates higher output voltage value, at reduced component-count, than other topologies, for a specified number of dc input voltages. For two cascaded modules, simulation and experimental verifications are carried out on the proposed inverter topology for an R-L load.  http://dx.doi.org/10.4314/njt.v39i2.30